The Correlation between Self-Confidence and Anxiety in encounter the Work Environment of Final Semester Students - Dino Dimenggo; Frischa Meivilona Yendi (Universitas Negeri Padang, 2021)
This study aims to determine the correlation between self-confidence and anxiety in encounter the work environment, in the final semester students of the Department of Guidance and Counseling, Faculty of Education, Universitas Negeri Padang (UNP). Self-confidence is one of the important things that final semester students must have to anxiety in encounter the work environment, and has an important role so that students are not too anxious in the work environment, because with high self-confidence which can be seen from the aspect of self-confidence it will make students more confident in the work environment. This research is a descriptive correlational study, with a sample of 123 students who were obtained using the Stratified Random Sampling technique. The data correlation instrument used a scale questionnaire that was compiled by itself in data collection using a Google form. The results of the data analysis of this study indicate that there is a significant negative correlation in the moderate category between self-confidence and anxiety in encounter the work environment in the final semester students of the Guidance and Counseling Department, Faculty of Education, UNP.